2022
DOI: 10.1177/09636897221124481
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Human Organ Development and Diseases With Fetal Tissue–Derived Organoids

Abstract: Recent advances in human organoid technology have greatly facilitated the study of organ development and pathology. In most cases, these organoids are derived from either pluripotent stem cells or adult stem cells for the modeling of developmental events and tissue homeostasis. However, due to the lack of human fetal tissue references and research model, it is still challenging to capture early developmental changes and underlying mechanisms in human embryonic development. The establishment of fetal tissue–der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…Re-epithelialization of the endometrium is an efficient process that provides scar-free healing and repair. The extreme regenerative capacity of the endometrium is based on the presence of progenitors, located in the epithelial and stromal cell compartments of the basalis layer 18 , 19 , 20 . A previous study demonstrated that intrauterine transplantation of EEOs effectively repaired the basal layer of the endometrium in an IUA mice model and conducted the intact endometrium 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Re-epithelialization of the endometrium is an efficient process that provides scar-free healing and repair. The extreme regenerative capacity of the endometrium is based on the presence of progenitors, located in the epithelial and stromal cell compartments of the basalis layer 18 , 19 , 20 . A previous study demonstrated that intrauterine transplantation of EEOs effectively repaired the basal layer of the endometrium in an IUA mice model and conducted the intact endometrium 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PSC‐derived organoids are generally naïve, resembling fetal tissues, which can be considered as excellent models for organogenesis research 53 . ESC‐derived organoids are more mature than iPSC‐derived organoids, which can be used as novel models for studying later phases of organogenesis 54,55 . However, ESCs need to be obtained from the embryo and there are many ethical issues involved (Figure 2).…”
Section: Cell Sources Of Organoidmentioning
confidence: 99%
“… 53 ESC‐derived organoids are more mature than iPSC‐derived organoids, which can be used as novel models for studying later phases of organogenesis. 54 , 55 However, ESCs need to be obtained from the embryo and there are many ethical issues involved (Figure 2 ).…”
Section: Cell Sources Of Organoidmentioning
confidence: 99%
“…[35] These structures exhibit high genetic stability and expansion yield, making them excellent candidates for tissue engineering of clinically relevant-sized structures that exhibit highly predictive functions compared to their native counterpart. [23,[36][37][38] The striking cellular organization similarities to native tissues, and the possibility to obtain these cell assemblies from most tissues in the human body have made organoids one of the most promising preclinical model candidates in recent years, with great strides in the understanding of organ development, [36,[39][40][41][42] as well as human genetic and developmental pathologies. [36,38,[40][41][42][43][44][45][46][47][48][49][50] As organoids can also be obtained from primary cells (i.e., obtained from biopsies) these tissue models have also facilitated the advancement of patient specific 1 biomedical research, and enabled further understanding and treatment development of rare diseases.…”
Section: Biofabricated Modelsmentioning
confidence: 99%
“…[23,[36][37][38] The striking cellular organization similarities to native tissues, and the possibility to obtain these cell assemblies from most tissues in the human body have made organoids one of the most promising preclinical model candidates in recent years, with great strides in the understanding of organ development, [36,[39][40][41][42] as well as human genetic and developmental pathologies. [36,38,[40][41][42][43][44][45][46][47][48][49][50] As organoids can also be obtained from primary cells (i.e., obtained from biopsies) these tissue models have also facilitated the advancement of patient specific 1 biomedical research, and enabled further understanding and treatment development of rare diseases. [37,39,51] In combination with genome editing technologies [52][53][54] and other emerging biomedical tools, organoids are sure to bring about a revolution in the biomedical research field and have the potential to shape the next generation of in vitro models.…”
Section: Biofabricated Modelsmentioning
confidence: 99%